Risk factors and evaluation of occupational fatigue among logistic truck drivers in Malaysia - Hasan, Atikah; Mohd Tamrin, Shamsul Bahri (Elsevier, 2022)
Majority of transport and logistic drivers greatly affected by fatigue. Fatigue and its associated risk factors are the causative factor for accidents, injuries and death in a wide range of workplace accidents. In fact, the effect of fatigue further resulted in performance degradation, lowered productivity and impaired health. The present study is aimed to determine the prevalence and risk factors associated with fatigue drivers in logistic company. In this cross-sectional study, data were collected using questionnaire including questions related to socio-demographic and occupational characteristics. Swedish Occupational Fatigue Inventory (SOFI) was used to assess subjective level of fatigue. A questionnaire was answered by 181 truck drivers employed in the logistic company. The result showed that the prevalence of fatigue is 41.3% over the past 12 months. On average, truck drivers completed over 200 km driving per day (49%). The mean values of the occupational fatigue level by categories were lack of energy (5.28), physical exertion (4.20), physical discomfort (3.33), lack of motivation (3.27) and sleepiness (3.22) respectively. The major causes of driving fatigue were associated with sleep deprivation (77.9%), traffic congestion (67.4%) and prolonged driving hours (60.8%). Job stress was found to be strongly associated with occupational fatigue (p<0.001).